Using Literature to Create the Novel “Ruthailak” - Nookur, Kreekamon (Academic and Research Journal of Liberal Arts (Online), 2021)
The aim of this research was to study the use of Thai literature in the creation of novel “Ruthailak” by Kornrumpa. The result indicated that 4 Thai literatures were applied, consisting of Ramayana, Enau, Sakuntala, and Honwinchai-Khawi. Creating a storyline through Ramayana (episode Battle Kumphakan), and the creation of characters from various literatures. These were all referenced from the above literatures. The author interestingly applied Thai literatures in terms of using the characters background, adjusting and adding details to be feasible and reasonable. Therefore, Ruthailak, created from Thai literature, was interesting because it didn’t only showed techniques of using literature to create plot and characters in the novel, but also expanded the perspective of literature.